FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH CADANGAN EURO DI INDONESIA - Navik Istikomah (Jurnal Ekonomi-Qu, 2018)
This research exposes about "Factors Affecting the Amount of Reserves Euro in Indonesia "with variables that will be related to interest rates, inflation rate, and exports. Theoretically, the results of this study are expected to provide contribution of ideas to the development of economics, especially regarding factors which affects the amount of Euro reserves in Indonesia. Practically, the results of this study expected to be made a recommendation for parties interested in regarding problem of factors that affect the amount of Euro reserves in Indonesia. In accordance with the objectives to be achieved, then the method used in this study is an Explanatory Survey, a method that explains the causal relationship between variables which was examined through hypothesis testing. The data analysis technique used is multiple regression to predict the value of the dependent variable for changes in certain values of three independent variables. The results of the study show that both partially and simultaneously, interest rates, inflation, and exports affect the amount of Euro reserves in Indonesia. Through value determinant coefficient is known that all three independent variables can explain variations in change the dependent variable is 78.8%, while the rest are explained by other variables. The phenomenon above, in line with what was conveyed by Levi (1997: 121) which states that "High the low foreign exchange reserves can be predicted by the inflation rate, domestic interest rates, and export value”